(untitled) (Journal of Engineering and Health Sciences, 2017)
Food and feeding was the main growth and production, and both of them become a major challenge in aquaculture development. The way adjustment of food delivery to pond is a important role to get the maximum return or profit to aquaculture entrepreneurs. This project represents an investigation about the fish feeding system. A system device to feed fish at predetermined amounts of food and time. A system that designed which has a computer monitored system which was developed in order to manage and control the system with real time. The aim of the project is to monitor and control the fish feeding system. This project is a simulation and experimental investigation into the development of PID controller using Matlab/Simulink software. The simulation development of the PID controller with the mathematical model of fish feeder system is done using trial and error method. The PID parameter is to be tested with an DC motor in Matlab/Simulink software. For the system, the best value of PID controller is when Kp = 100, Ki = 0.05 and Kd = 25. When Kp = 100 the rise time is a 0.113 second, when Ki = 0.05 the rise time is at 0.151 second and when Kd = 25, the rise time is a 0.143 second.